A Revision of Afrotropical Species of the Eupyrgota (Diptera, Pyrgotidae): the varipennis and melancholica Subgroups of Species - Korneyev, V.A. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2006)
Based on the study of the type specimens described by
C. Curran, E. Brunetti, G. Enderlein and P. Vanschuytbroeck and exhaustive material from many entomological collections, the species of the varipennis and melancholica subgroups of Eupyrgota
Coquillett are redescribed and a key to all the species occurring in the Afrotropical Region and Arabian Peninsula is provided. Eupyrgota echinata Korneyev, sp. n. from the Democratic Republic of Congo and Uganda and Eupyrgota crassipes Korneyev, sp. n. from the Democratic Republic of Congo are described. The following synonymy is established. Eupyrgota Coquillett, 1898 = Peltodasia Enderlein, 1942, syn. n. The following species are transferred to Eupyrgota: E. varipennis (Curran, 1928), comb. n.,
from Campylocera Macquart; and E. vespiformis (Enderlein, 1942), comb. n. from Peltodasia Enderlein. E. rugosigenis Hendel is resurrected from synonymy. The host species of Eupyrgota latipennis Walker is
recorded for the first time: the adult beetle Pachnoda interrupta Olivier (Coleoptera, Cetoniidae). This is the first host record for any representative of the genus Eupyrgota and for any Afrotropical pyrgotids. На основании изучения типовых материалов, описанных Ч. Кэреном, Ю. Брунетти, Г. Эндерляйном и П. Вансхётбруком и исчерпывающих материалов из многочисленных энтомологических коллекций, представлены описания видов из подгрупп varipennis и melancholica и таблица для определения видов рода Eupyrgota Coquillett, встречающихся в Афротропической области и на Аравийском полуострове. Описаны Eupyrgota echinata Korneyev, sp. n. из Демократической Республики Конго и Уганды и Eupyrgota crassipes Korneyev, sp. n. из Демократической Республики Конго. Установлена следующая синонимия. Eupyrgota Coquillett, 1898 = Peltodasia Enderlein, 1942, syn. n. Eupyrgota varipennis (Curran, 1928), comb. n. и Eupyrgota vespiformis (Enderlein, 1942), comb. n. перемещены соответственно из Campylocera Macquart и Peltodasia Enderlein. E. rugosigenis Hendel восстановлена из синонимии. Впервые указан хозяин Eupyrgota latipennis Walker — взрослая бронзовка Pachnoda interrupta Olivier (Coleoptera, Cetoniidae); это также первое указание хозяина для видов рода Eupyrgota и для афротропи-ческих пирготид.